The health consequences of stigma and discrimination: a systematic review and meta-analysis of their impact on Black non-binary individuals in Sub-Saharan Africa - Ikhile, Ikekhwa Albert; Mavhandu-Mudzusi, Azwihangwisi Helen (Frontiers in Sociology, 2025)
IntroductionBlack non-binary individuals in Sub-Saharan Africa experience pervasive stigma and discrimination, which negatively influence their health outcomes. Despite the significance of these challenges, their unique lived experiences remain underreported within public health research. This study sought to systematically investigate the health consequences of stigma and discrimination on this marginalized population.MethodA systematic review was conducted in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The review incorporated 15 peer-reviewed studies from 13 Sub-Saharan African countries. Data extraction focused on three domains: mental health outcomes, physical health vulnerabilities, and barriers to accessing and utilizing healthcare services.FindingsThe review highlighted a profound mental health burden within the population, with 74% of participants exhibiting symptoms of depression, 65% reporting anxiety, and 45% experiencing suicidal ideation. Physical health vulnerabilities included heightened risks of sexually transmitted infections (STIs) and chronic conditions such as hypertension and diabetes. These health risks were compounded by systemic discrimination and restricted access to healthcare. Notably, 75% of participants reported challenges in accessing gender-affirming healthcare services. Key barriers included healthcare provider bias, the absence of culturally competent services, and broader systemic inequities across healthcare systems.ConclusionThis study underscores the urgent need for targeted, evidence-based interventions to address the disproportionate health burdens faced by Black non-binary individuals in Sub-Saharan Africa. It further emphasizes the importance of implementing inclusive healthcare policies and culturally competent practices to ensure equitable health outcomes for this underserved population.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251080364.